Religious participation of Christians and muslims fostering mutual social trust in Nigeria? : an exploration theological study - Bandele, Oluwafemi Ayodele (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPhil)--Stellenbosch University, 2014.